Distribution and Identification of Ulva aragoensis (Ulvaceae, Chlorophyta), a Constituent Species of Green Tides in the Southern Yellow Sea, Based on Molecular Data - Yichao Tong; Lihua Xia; Jinlin Liu; Shuang Zhao; Yuqing Sun; Tingjian Wu; Zhangyi Xia; Shuang Li; Jiaxing Cao; Jianheng Zhang (Journal of Marine Science and Engineering, 2022)
Green tides are a serious global ecological disaster; the largest occur in the Southern Yellow Sea (SYS). Early-stage green tides in the SYS are composed of four species (Ulva prolifera, Ulva flexuosa, Ulva linza, and Ulva compressa). We found that U. aragoensis is a constituent species of green tides in the SYS based on molecular data. Furthermore, this study re-evaluated the proportion of U. aragoensis in green tides and found that it was more prevalent in micro-propagules cultured from surface seawater during an early-stage green tide in 2021. The internal transcribed spacers, tufA, 18S, rbcL, large subunit, psbA, and rps2-trnL gene sequences were compared; the tufA and rbcL gene sequences were the most suitable DNA barcodes for distinguishing U. aragoensis. A haplotype analysis of the sequences of floating U. aragoensis and its micro-propagules was performed to study the correlation between green tide macroalgae and micro-propagules; close haplotype similarities occurred between them. This study further clarified the species composition of SYS green tides and provided a reference for assessing the relationship between micro-propagules and green tide macroalgae.